Comparison of the Marginal Bone Loss in One-stage versus Two-stage Implant Surgery - Rasoul Gheisari; Hesamuddin Eatemadi; Akram Alavian (Shiraz University of Medical Sciences, 2017)
Statement of the Problem: Dental implant is one of the best choices for reconstruction of aesthetic and function. High success rate of these treatments are related to some considerations such as case selection, implant system selection and surgical methods. One-stage or two-stage surgical approaches are routine surgical methods in dental implant treatments. The minimum rate of bone loss around fixtures is the most important criteria for evaluation of implant treatment success that can be affected by different methods of surgery. Purpose: This experimental study has been done to compare the crestal bone loss at mesial and distal surface of implants installed through either one-stage or two-stage surgical approach. Materials and Method: In the present randomized clinical trial, 310 Astra Tech implant system were divided into two unequal groups to be used for 140 patients. One hundred and seventy implants were inserted through one-stage and 140 through two-stage surgical approach. The baseline parallel periapical radiography was provided immediately after the surgery. Six months after the functional loading, another radiographic image was provided by using the same technique and machine. Marginal bone loss was calculated by using Adobe Photoshop CS5 software. Data were statistically analyzed with SPSS software. P values less than 0.05 were considered as significant. Results: The mean Bone loss on the mesial and distal surfaces of implants inserted through one-stage surgery and two-stage surgery was 0.76±0.04 and 0.842±0.04 mm respectively. No notable marginal bone change was observed between the maxilla (0.860mm) and mandible (0.729mm). Moreover, p Value was>0.05 in all samples, indicating no significant difference in the crestal bone loss. Conclusion: Accordingly, one-stage surgical technique may provide better esthetic and function for dental implants. There is no significant difference between the two approaches concerning the marginal bone loss.